Managing K-Pop Impressions on BTS ARMY Fandom in Jakarta - Firenza, Jessica; Menayang, Alfred Pieter (Journal of Humanities and Social Sciences Studies, 2023)
K-Pop gained popularity in Indonesia through Korean dramas featuring songs sung by Korean singers. Indonesian K-Pop fans, especially the BTS group, the popularity of BTS amazed many fans and wanted to imitate everything BTS did to make them look like them. Behind it all, these fans live between as a fan and as ordinary people who carry out activities like other people in general. The theory used is impression management theory by Erving Goffman, which states that individuals must form and uphold an image that is in line with the role they want to present to the public, and the concept of dramaturgy theory which compares human interaction with theatrical performances with individuals playing specific roles to achieve goals, they are the front stage, middle stage, and backstage. Research on this topic uses impression management theory and dramaturgical theory, which explain that individuals and organizations present themselves in a certain way to achieve their goals. This research follows a constructivist paradigm and uses qualitative methods like participatory observation, interviews, and documentation.